2021
DOI: 10.2147/jhc.s303588
|View full text |Cite
|
Sign up to set email alerts
|

The Crosstalk Between Cancer Cells and Neutrophils Enhances Hepatocellular Carcinoma Metastasis via Neutrophil Extracellular Traps-Associated Cathepsin G Component: A Potential Therapeutic Target

Abstract: Background: Emerging evidences have highlighted the roles of neutrophils, as the major host microenvironment component, in the development of hepatocellular carcinoma (HCC). Neutrophils extracellular traps (NETs) produced in the infection can strengthen the behavior of cancer metastasis. Here, we investigated the roles of NETs in HCC metastasis and further explore the underlying mechanism of how NETs interact with cancer. Methods: The neutrophils were isolated from whole blood of HCC patients and used to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 51 publications
0
29
0
Order By: Relevance
“…Pre-clinical and clinical evidence directly implicating CG in resistance to therapy is scant, yet the protein is known to drive ECM remodeling and angiogenesis, which are mechanisms associated with cancer progression and resistance to therapy ( Figure 1 ) [ 3 , 114 , 115 ]. Furthermore, there exists evidence associating cathepsin G expression with an aggressive neoplastic phenotype that is associated with treatment resistance [ 116 , 117 ]. Further research is needed, however, to elaborate any cathepsin G-dependent processes that may influence such resistance to therapy.…”
Section: Net Components In Cancer Therapy Resistancementioning
confidence: 99%
“…Pre-clinical and clinical evidence directly implicating CG in resistance to therapy is scant, yet the protein is known to drive ECM remodeling and angiogenesis, which are mechanisms associated with cancer progression and resistance to therapy ( Figure 1 ) [ 3 , 114 , 115 ]. Furthermore, there exists evidence associating cathepsin G expression with an aggressive neoplastic phenotype that is associated with treatment resistance [ 116 , 117 ]. Further research is needed, however, to elaborate any cathepsin G-dependent processes that may influence such resistance to therapy.…”
Section: Net Components In Cancer Therapy Resistancementioning
confidence: 99%
“…The presence of TANs supports the development of HCC via direct crosstalk with cancer cells. They release neutrophil extracellular traps (NETs), which support tumor growth by secretion of MMP-9 and cathepsin G, as well as the induction of metastasis of HCC cells [ 105 ]. Therefore, NETs can be potential targets for the new treatment options in HCC [ 106 ].…”
Section: Components Of the Tme In Hccmentioning
confidence: 99%
“…In a study, NETs were found to drive the transformation of typical epithelial morphology to the mesenchymal phenotype and increase the expression of tumor stem cell-related markers in human breast cancer MCF7 cells, which was accompanied by enhanced invasion and migration ability ( 8 ). In addition, NET-associated cathepsin G has been reported to facilitate the invasion and metastasis of HCC cells both in vitro and in vivo ( 69 ). The DNA component of NETs can directly act on the CCDC25 receptor on the surface of cancer cells and activates the ILK–β-parvin cascade to enhance the motor capacity of cells ( 70 ).…”
Section: Nets Promote Colorectal Cancer Development and Metastasismentioning
confidence: 99%